1994
DOI: 10.1038/368864a0
|View full text |Cite
|
Sign up to set email alerts
|

MHC class l/β2-microglobulin complexes associate with TAP transporters before peptide binding

Abstract: Major histocompatibility complex class I molecules bind antigenic peptides in the endoplasmic reticulum (ER) and transport them to the cell surface for recognition by cytotoxic T lymphocytes. The peptides are predominantly generated from cytoplasmic proteins, probably by the action of the multicatalytic proteinase complex, or proteasome. They are transported into the ER by the transporters associated with antigen processing (TAP), a complex formed from two subunits, TAP.1 and TAP.2 (refs 3-5). Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
206
1
2

Year Published

1995
1995
2003
2003

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 351 publications
(221 citation statements)
references
References 27 publications
12
206
1
2
Order By: Relevance
“…The footprint of each domain in the ring (22 ϫ 56 Å) would correspond well with the space required for 7-8 transmembrane helices and short connecting loops (18,19,22) and also matches the (slightly smaller) footprint of the six TMD helices in the half-transporter MsbA (29). This area is most likely to contain the domains in closest proximity to the MHC class I binding grooves awaiting suitable peptides (40,55,56) and is also the most likely target area for the interaction of US6, the viral inhibitor of TAP expressed by human cytomegalovirus (51,57). The threedimensional structures of TAP and P-glycoprotein appear less similar from the cytoplasmic side/intracellular views ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The footprint of each domain in the ring (22 ϫ 56 Å) would correspond well with the space required for 7-8 transmembrane helices and short connecting loops (18,19,22) and also matches the (slightly smaller) footprint of the six TMD helices in the half-transporter MsbA (29). This area is most likely to contain the domains in closest proximity to the MHC class I binding grooves awaiting suitable peptides (40,55,56) and is also the most likely target area for the interaction of US6, the viral inhibitor of TAP expressed by human cytomegalovirus (51,57). The threedimensional structures of TAP and P-glycoprotein appear less similar from the cytoplasmic side/intracellular views ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was also shown that a chaperone molecule, calnexin, mediates heavy-chain-P2-m dimerisation and binding of the dimers to TAP molecules facilitates their assembly with TAP-transported peptides. (Trowsdale et al, 1990;Kleijmeer et al, 1992;Spies et al, 1992;Ortman et al, 1994).…”
mentioning
confidence: 99%
“…Fax +49 6221 563953. Brenner, 1994) and peptide transporters (Ortmann et al, 1994;Suh et al, 1994), stable association with fl2m (Kvist & Hamann, 1990), and binding of the antigenic peptide that is held in the polymorphic peptide binding groove. MHC class I molecules lacking peptide display a different conformation and are deficient with respect to surface transport and stability (Hsu et al, 1991 ;Lie et aI., 1990).…”
Section: Introductionmentioning
confidence: 99%